The Effect of Stocking Density on Growth and Survival Rate of Bullfrog Tadpoles - Singpa, Bounlam; KANDEE, Thanousinh; Tayamad, Khambou; PHANPUOMMA , Boaukeo (Souphanouvong University Journal Multidisciplinary Research and Development, 2020)
The effect of stocking density on growth and survival rate of Bullfrog (Rana catesbeiana) Tadpoles in concrete tanks (90 cm and 20 cm of water level) with 80% was applied. The one week tadpoles with average weight of (0.12 g were stocked at 3 stocking density of 60, 120 and 240 individually/tanks for 20 days. They were fed to appearance satiation with 40% protein at 10% 0f body weight twice a day. The results indicate that tadpoles developed two legs at 18 day and foot legs at 28 days. The mean weight gained by the experimental tadpoles were 1.45±0.03, 1.24±0.05 and 1.06±0.03 g, respectively. The average daily weight gained by the experimental tadpoles were 0.073±0.001, 0.052±0.001 and 0.053±0.001g day-1, respectively. The results indicate that at the end of the experiment, growth of the tadpoles was significantly difference among 3 stocking densities (P<0.05), with the survival rate of 31.11±1.92, 21.94±1.27 and 17.78±0.87 %, respectively (P<0.05).